Antimicrobial, antioxidant, and waterproof RTV silicone-ethyl cellulose composites containing clove essential oil. (15th July 2018) - Heredia-Guerrero, José A.; Ceseracciu, Luca; Guzman-Puyol, Susana; Paul, Uttam C.; Alfaro-Pulido, Alejandro; Grande, Chiara; Vezzulli, Luigi; Bandiera, Tiziano; Bertorelli, Rosalia; Russo, Debora; Athanassiou, Athanassia; Bayer, Ilker S.
Highlights: PDMS and ethyl cellulose can be blended in solution to form composites. PDMS increases the hydrophobic behavior of ethyl cellulose-based composites. Antioxidant and antimicrobial properties are achieved by addition of clove oil. Abstract: Ethyl cellulose (EC)/polydimethylsiloxane (PDMS) composite films were prepared at various concentrations of PDMS in the films (0, 5, 10, 15, and 20 wt.%). Morphological and chemical analysis by EDX-SEM and ATR-FTIR showed that EC-rich matrices and PDMS-rich particles were formed, with the two polymers interacting through Hbonds. The number and diameter of particles in the composite depended on the PDMS content and allowed a fine tuning of several properties such as opacity, hydrophobicity, water uptake, and water permeability. Relative low amounts of clove essential oil were also added to the most waterproof composite material (80 wt.% ethyl cellulose and 20 wt.% PDMS). The essential oil increased the flexibility and the antioxidant capacity of the composite. Finally, the antimicrobial properties were tested against common pathogens such as Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa . The presence of clove essential oil reduced the biofilm formation on the composites.